Magnetic resonance spectroscopy evaluation in patients with neuromyelitis optica. Issue 4 (1st April 2010) - de Seze, Jérôme; Blanc, Frédéric; Kremer, Stéphane; Collongues, Nicolas; Fleury, Marie; Marcel, Christophe; Namer, Izzie-Jacques
Abstract : Objective: Neuromyelitis optica (NMO) is an inflammatory disease associated with optic neuritis and myelitis. Although some studies have reported multiple sclerosis (MS)-like lesions in 10–30% of NMO patients, brain MRI is usually normal. Several studies have observed metabolic abnormalities on MR spectroscopy in MS, even in normal-appearing white matter (NAWM). To the authors' knowledge, MR spectroscopy has never been used to investigate NMO. The aim of this study was to evaluate metabolic abnormalities in the NAWM and normal-appearing grey matter (NAGM) of NMO patients. Methods: The authors evaluated 24 patients (17 women and seven men, with a mean age of 44.6 years). NMO was diagnosed according to revised criteria. All patients had a brain and spinal cord MR imaging including MR spectroscopy sequences in both NAWM and NAGM. Patients were compared with 12 healthy subjects. Results: NAA/creatinine ratios in NAWM (1.89±0.26 in NMO compared with 1.91±0.15 in control subjects) and NAGM (1.62±0.21 compared with 1.59±0.18) were normal, as were choline/creatinine ratios in NAWM (1.03±0.18 compared with 1.08±0.14) and NAGM (0.89±0.2 compared with 0.94±0.2). Myo-inositol values in NAWM were also normal (0.42±0.12 compared with 0.42±0.18). Conclusion: Our results are clearly different from those found in MS, where NAA is frequently decreased and choline increased, even in NAWM. Our findings could have an impact on the differentiation between MS and NMO.